2021
DOI: 10.1111/wrr.12985
|View full text |Cite
|
Sign up to set email alerts
|

Role of haematopoietic cell‐specific protein 1‐associated protein X‐1 gene in lipopolysaccharide‐induced apoptosis of human dermal fibroblasts

Abstract: Wound healing may be disrupted by lipopolysaccharide (LPS)‐induced mitochondrial dysfunction, inflammation, and excessive oxidative stress, which can lead to undesirable consequences. The haematopoietic cell‐specific protein 1‐associated protein X‐1 (HAX‐1) is a mitochondrial matrix protein that regulates mitochondrial function. This study aimed to comprehensively identify the role of HAX‐1 in the inhibition of LPS‐induced mitochondrial dysfunction and apoptosis in human dermal fibroblasts (HDFs). HAX‐1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…crucial initial factor in wound healing (Ninan et al, 2015;Visan, 2019) and fibroblasts are deemed to play an essential role in this process (Desjardins-Park et al, 2018;Visan, 2019), the relationship and mechanisms between fibroblasts and LPS exposure remain less well defined. In our present study, we used LPS (500 ng/ml, 24 h) to mimic inflammatory stimulation in vitro during wound healing with a superimposed infection, because appropriate LPS stimulation could activate inflammatory response and start wound healing (Landén et al, 2016;Li et al, 2017), whereas inappropriate dose or treatment time of LPS may not promote wound healing, or even delay wound healing due to excessive oxidative stress or severe infection (Ning et al, 2021). We found that LPS induced elevated stathmin expression and promoted HDF migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…crucial initial factor in wound healing (Ninan et al, 2015;Visan, 2019) and fibroblasts are deemed to play an essential role in this process (Desjardins-Park et al, 2018;Visan, 2019), the relationship and mechanisms between fibroblasts and LPS exposure remain less well defined. In our present study, we used LPS (500 ng/ml, 24 h) to mimic inflammatory stimulation in vitro during wound healing with a superimposed infection, because appropriate LPS stimulation could activate inflammatory response and start wound healing (Landén et al, 2016;Li et al, 2017), whereas inappropriate dose or treatment time of LPS may not promote wound healing, or even delay wound healing due to excessive oxidative stress or severe infection (Ning et al, 2021). We found that LPS induced elevated stathmin expression and promoted HDF migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%